An analysis of postoperative hemoglobin levels in patients with a fractured neck of femur - Navraj S. Nagra; Dmitri van Popta; Sigrid Whiteside; Edward M. Holt (Acta Orthopaedica et Traumatologica Turcica)
Objectives: The aim of this study was to analyze the changes in hemoglobin level and to determine a suitable timeline for post-operative hemoglobin monitoring in patients undergoing fixation of femoral neck fracture. Patients and methods: Patients who underwent either dynamic hip screw (DHS) fixation (n = 74, mean age: 80 years) or hip hemiarthroplasty (n = 104, mean age: 84 years) for femoral neck fracture were included into the study. The hemoglobin level of the patients was monitored perioperatively. Results: Analysis found a statistically and clinically significant mean drop in hemoglobin of 31.1 g/L over time from pre-operatively (D0) to day-5 post-operatively (p < 0.001), with significant reductions from D0 to day-1 and day-1 to day-2 (p < 0.001). At each post-operative time point, DHS patients had lower hemoglobin values over hemiarthroplasty patients (p = 0.046). Conclusion: The decrease in hemoglobin in the first 24-h post-operative period (D0 to day-1) is an underestimation of the ultimate lowest value in hemoglobin found at day-2. Relying on the day-1 hemoglobin could be detrimental to patient care. We propose a method of predicting patients likely to be transfused, and recommend a protocol for patients undergoing femoral neck fracture surgery to standardize postoperative hemoglobin monitoring. Level of evidence: Level IV Prognostic study. Keywords: Fracture, Hemoglobin, Neck of femur, Postoperative